ANALISIS PERUBAHAN KEBIJAKAN LUAR NEGERI AMERIKA SERIKAT DALAM PARIS AGREEMENT PADA MASA PEMERINTAHAN JOE BIDEN - Fuad Rizki Satriyo; Ika Riswanti Putranti; Muhammad Faizal Alfian (Journal of International Relations, 2023)
The change in leadership from Donald Trump to Joe Biden brought a new policy direction for the United States. One of them is the Paris Agreement. Biden's concern for the issue of climate change led the United States to change its foreign policy in the Paris Agreement, namely ratification after it was previously issued during the Trump administration. This study presents the formulation of the problem "How can changes in US foreign policy in the Paris Agreement in the era of Joe Biden be seen through green theory?". Through the formulation of the problem, this study explains how green theory sees changes in US foreign policy in the Paris Agreement during the reign of Joe Biden. This research is a qualitative type with explanatory data analysis techniques. In conducting research, green theory and the Holsti foreign policy analysis model are used to explain how the role of the leader as the main actor influences the making of a country's foreign policy. This research found that the difference in policy focus between Trump and Biden was a factor in the change in US foreign policy in the Paris Agreement during the reign of Joe Biden.